(untitled) (Research, Society and Development, 2023)
Objective: To analyze the scientific production on the role of nurses in health education in obesity. Method: This is an integrative review in which six stages were covered: selection of the research question; literature search; data categorization; analysis of studies included in the review; interpretation and synthesis of results and presentation of the review. The databases were: Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature in Health Sciences (Lilacs) and Database in Nursing (BDENF). The strategy was based on the acronym PICo. In this sense, the following research question was formulated: What was produced in the literature about the role of nurses in health education with obesity? Results: four studies were selected, all of which were produced in Brazil, two in 2017 and two in 2020. The studies included in this review highlighted the following themes: the role of nurses in health education in the prevention and control of obesity by through guidance on healthy living habits and multidisciplinary team work. Conclusion: This study contributed to help update professionals in the role of nurses in health education with obesity, adding essential guidelines such as; teamwork, making the population aware through projects, prevention and control of obesity, through healthy habits and physical exercises, thus minimizing the health risks of obese people or people who are overweight.